2022
DOI: 10.3390/v14020359
|View full text |Cite
|
Sign up to set email alerts
|

Encephalomyocarditis Virus 2A Protein Inhibited Apoptosis by Interaction with Annexin A2 through JNK/c-Jun Pathway

Abstract: Encephalomyocarditis virus can cause myocarditis and encephalitis in pigs and other mammals, thus posing a potential threat to public health safety. The 2A protein is an important virulence factor of EMCV. Previous studies have shown that the 2A protein may be related to the inhibition of apoptosis by virus, but its specific molecular mechanism is not clear. In this study, the 2A protein was expressed in Escherichia coli in order to find interacting cell proteins. A pull down assay, coupled with mass spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Moreover, published data showed that the deletion of 2A results in the apoptosis of EMCV-infected BHK-21 cells [ 30 ]. 2A may inhibit the chemical-induced apoptotic death of PK15 and BHK-21 cells via its ectopic expression [ 31 ]. All the described investigations included the study of one protein in a particular cell culture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, published data showed that the deletion of 2A results in the apoptosis of EMCV-infected BHK-21 cells [ 30 ]. 2A may inhibit the chemical-induced apoptotic death of PK15 and BHK-21 cells via its ectopic expression [ 31 ]. All the described investigations included the study of one protein in a particular cell culture.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of 2A interference in cell death is still unclear. There is only one experimentally based assumption about mechanism: EMCV 2A plays an antiapoptotic role by interaction with Annexin A2 [ 31 ]. Nevertheless, this proposition is based on a 2A-expressing model, not a viral-infecting model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of the transactivator Tas encoded by foamy viruses and expressed after cell cycle arrest or before apoptosis highlight the different mechanisms through which virus–host interactions inhibit cell proliferation [ 21 ]. Encephalomyocarditis virus 2A protein inhibited apoptosis [ 22 ], and human papilloma virus 16 (HPV16) protein E7 increased PKM2 expression and activated the nonglycolytic function of PKM2 to promote cervical cancer cell proliferation [ 23 ]. However, no direct evidence has shown to date that the V protein encoded by NDV regulates host cell proliferation; however, our present work shows that the V protein promotes cancer cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The P2 and P3 precursor proteins are processed to generate the non-structural proteins 2A, 2B, 2C, 3A, 3B (Vpg), 3C protease, and the RNA-dependent RNA polymerase 3D ( Palmenberg et al, 1984 ). Among these viral proteins, AnxA2 is known to interact with the virulence protein 2A, which is required for viral pathogenesis and inhibition of apoptosis through the JNK/c-Jun pathway, promoting EMCV replication during the early stage of infection ( Carocci et al, 2011 ; Han et al, 2022 ). ii) Enterovirus 71 (EV71) .…”
Section: Impact Of Anxa2 On Virus Life Cyclementioning
confidence: 99%